The influence of prior knowledge on a consumer's current judgment in rating a hotel / Muhammad Fauzi Abdul Ghani - Abdul Ghani, Muhammad Fauzi (2009)
Knowledge in consumer judgment is essential for a firm to stay competitive in business especially in the era of globalization. The findings from many researches in the field of consumer judgment showed that the current judgment is influenced by the prior knowledge. Most studies carried out to date in this area focused mainly on the goods and still many areas in service domain have yet to be explored. In view of this and the rapid emergence of the service industry, the study focuses on the influence of prior knowledge on the current judgment in the service industry and the focus is on the hotel industry. The study is challenging as hotel has both the tangible and intangible dimensions at an almost equally balance. Hotel is chosen as it is a major sector in the service industry. In hotel, the tangible dimension is associated with the physical evidence of the building, lobby, reception, guest room and restaurant while the intangible dimension is associated with the service interaction between the hotel customers and the hotel employees. The study is significant as it covers both the tangible and intangible dimensions which is so beneficial to hotel firms in business decision and marketing and also to enrich the present knowledge in the fields of psychology and service marketing. The study suggests that the current judgment in hotel industry is influenced by the prime type (tangible vs. intangible) and the context extremity (extreme vs. moderate). The study was carried out by an experiment and the subjects for the experiment were among the graduate students.